A revision of the Metaphire peguana species-group (Oligochaeta: Megascolecidae) from Vietnam - Nguyen, Tung T.; Lam, Dang H.; Nguyen, Anh D. (Zootaxa, 2023)
The Metaphire peguana species-group was revised from the earthworm fauna of Vietnam. As a result, a total of seven species/subspecies have been assigned to this species-gro+up, namely M. peguana peguana (Rosa, 1890), M. peguana laisonensis Nguyen & Nguyen, 2017, M. bahli (Gates, 1945), M. doiphamon Bantaowong & Panha, 2016, M. dorsomultitheca Nguyen & Nguyen, 2015, M. kiengiangensis Nguyen & Trinh, 2015, and M. nhuongi Nguyen, 2016. The species, M. pacseana (Thai & Samphon, 1988) was removed from the group. The species-group was diagnosed by having spermathecal pores in 6/7/8/9, sometimes 5/6/7/8/9 or 7/8/9; bithecate or polythecate; genital markings paired in 17/18 and 18/19 or in xvii and xix; accessory glands paired, coelomic, strongly covered by muscular-walled bursae; septum 10/11 only present ventrally; and intestinal caeca simple. The K2P genetic distances between the group members varies from 12.9% to 20.7%. The phylogenetic analysis clearly supports the members of this species-group.